PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN MEMILIH PELAYANAN RAWAT INAP DENGAN VARIABEL MODERATING TINGKAT PENDAPATAN KONSUMEN - Nesty Puspita Sari; Sugiyarmasto2 . (Universitas Sahid Surakarta, 2018)
Considering the development of hospital nowdays that is not only in social aspects but also in economi social ones make hospital to do marketing activities one of them is the marketing of hospital service which the activity is for costumer who want to use the hospital service, one of the service is the in patient service. The research aims at knowing the relation between mix marketing component and consumer’s incame rate to the consumer’s decision to choose the hospital in patient service in RSUP Dr. Soeradji Tirtonegoro Klaten. Teknique of sample collecting is using the purposive sampling and the research sample is 145 respondences from RSUP Dr. Soeradji Tirtonegoro. The data of analysis method uses the double regression analysis. Based on the data analysis result, can be concluded as follows: 1) the result of t test shows that product, price, process and the interaction between product and the income rate shows a signifcant result. The double regression analysis gets the model Y = 0,069 + 0,173X1 + 0,232X3 + 0,224X6 + 0,093X1M + e. 2) The result of f test which 7,790 > 1,75 shows that there is a signifcant inﬂuence between mix marketing variable and the income rate in together to the consumer’s decision. 3) The result of determination coefsisiency (R2) is 41,4%. It is inﬂuenced by the changes of component product, place, price, promotion, people, process, physical evidence, interaction between product and income rate, interaction between place an income rate, interaction between price and income rate, interaction between promotion an income rate, interaction between people and income rate, interaction between process and income rate, interaction between physical evidence and income rate. The rest of 58,6% is described by another component which was not observed in this research.